Typography - Crisp, Denise Gonzales; Temple, William F. (London : Thames and Hudson, 2012)
This volume frames typography as a system of interrelated concerns a s much as it summarises the traditional 'craft' that is the usual conte nt of books on typography. It describes the constantly shifting terrain of typography and provides ways of thinking about typographic relation ships that adapt to content, contexts, and audiences.
Relational systems -- Reading systems -- Formal systems -- Materiali ty -- Language systems -- The disorder of things.
Includes bibliographical references (p. 247) and index.
Keywords: Graphic design (Typography); Printing; Type and type-founding.